Detection of membrane-bound HLA-G translated products with a specific monoclonal antibody. - Bensussan, A (1995)
A monomorphic anti-HLA-G monoclonal antibody (mAb) was obtained by immunization of HLA-B27/human beta 2-microglobulin double-transgenic mice with transfected murine L cells expressing both HLA-G and human beta 2-microglobulin. This mAb, designated BFL.1, specifically recognizes, by flow cytometry analysis, the immunizing HLA-G-expressing cells, whereas it does not bind to parental untransfected or to HLA-B7- and HLA-A3-transfected L cells, suggesting that it distinguishes between classical HLA-A and -B and nonclassical HLA-G class I molecules. This was further assessed by the absence of BFL.1 reactivity with a number of human cell lines known to express classical HLA class I proteins. In addition, we showed that the BFL.1 mAb also labels HLA-G-naturally-expressing JEG-3 and HLA-G-transfected JAR human choriocarcinoma cell lines as well as a subpopulation of first-trimester placental cytotrophoblast cells. Further biochemical studies were performed by immunoprecipitation of biotinylated membrane lysates: BFL.1, like the monomorphic W6/32 mAb, immunoprecipitated a 39-kDa protein in HLA-G-expressing cell lines, a size corresponding to the predicted full-length HLA-G1 isoform. However, in contrast to W6/32, which immunoprecipitates both classical and nonclassical HLA class I heavy chains, BFL.1 mAb does not recognize the class Ia products. Such a mAb should be a useful tool for analysis of HLA-G protein expression in various normal and pathological human tissues and for determination of the function(s) of translated HLA-G products.